Carbon-coated europium-doped sodium ferric sulfate positive electrode material and preparation method thereof, sodium ion battery and electric equipment
By carbon coating and doping europium on sodium iron sulfate, the problem of poor conductivity of pure iron-based sulfate positive electrode materials is solved, significantly improving the discharge specific capacity and rate performance, and improving the electrochemical characteristics of sodium ion batteries.
Patent Information
- Application Number
- CN202411717090.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
Pure iron-based sulfate positive electrode materials have poor conductivity and low ion transfer rate, resulting in lower discharge specific capacity and poor rate performance.
By carbon-coated and doped with europium, a carbon-coated sodium ferrosulfate positive electrode material with europium doped with europium is formed to improve its conductivity and ion transport rate.
The discharge specific capacity and rate performance of the positive electrode material are significantly improved, and the electrochemical characteristics are improved, making it more suitable for sodium ion batteries.
Smart Images

Figure CN119542392A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sodium ion batteries, and in particular to a carbon-coated europium-doped sodium iron sulfate positive electrode material and a preparation method thereof, a sodium ion battery and electrical equipment. Background Art
[0002] In recent years, the depletion of lithium resources has led to a continuous rise in the price of lithium raw materials, which has significantly increased the production cost of lithium-ion batteries and limited the widespread application of lithium-ion batteries. In this context, it is particularly important to develop new low-cost, high-performance energy storage technologies. Sodium-ion batteries have abundant resource reserves (the sodium content in the earth's crust is about 2.7500%) and have a similar working principle to lithium-ion batteries, and have gradually become a research hotspot.
[0003] Among the positive electrode materials for sodium-ion batteries, sulfate materials have a higher redox potential and can provide a higher operating voltage, which can reach 3.8V, while maintaining a lower cost advantage. Among the many sulfate positive electrode materials, iron-based sulfate is considered one of the most promising candidate materials because of its low cost and high energy density potential.
[0004] However, pure iron-based sulfates are polyanionic positive electrode materials, which have poor electrical conductivity and low ion transmission rate, resulting in low discharge capacity and poor rate performance. Therefore, it is necessary to improve them. Summary of the invention
[0005] The purpose of the present application is to provide a carbon-coated europium-doped sodium iron sulfate positive electrode material and a preparation method thereof, a sodium ion battery and an electrical device to solve the above-mentioned problems.
[0006] To achieve the above objectives, this application adopts the following technical solutions:
[0007] A carbon-coated europium-doped sodium ferric sulfate positive electrode material, comprising a core and a carbon coating layer coating the core, wherein the core comprises europium-doped sodium ferric sulfate;
[0008] The chemical formula of the carbon-coated europium-doped sodium iron sulfate positive electrode material is Na 2.4 Fe 1.8-3x Eu x (SO4)3 / C, where 0<x≤0.1.
[0009] The present application also provides a method for preparing the carbon-coated europium-doped sodium iron sulfate positive electrode material as described above, comprising:
[0010] A sodium source, an iron source, a carbon source and a europium source are mixed and sintered in an inert gas atmosphere to obtain the carbon-coated europium-doped sodium iron sulfate positive electrode material.
[0011] According to an embodiment of the present application, the sodium source includes anhydrous sodium sulfate;
[0012] The iron source includes at least one of ferrous sulfate heptahydrate, ferrous sulfate monohydrate, and anhydrous ferrous sulfate;
[0013] The carbon source comprises at least one of graphene, graphite, Ketjen black, supper p, multi-walled carbon nanotubes, citric acid, glucose, sucrose, and ascorbic acid;
[0014] The europium source includes at least one of europium sulfate and europium carbonate.
[0015] According to an embodiment of the present application, the molar ratio of sodium in the sodium source to iron in the iron source and europium in the europium source is 2.4:(1.8-3x):x.
[0016] According to an embodiment of the present application, the mass of the carbon source accounts for 1% to 12% of the total mass of the sodium source and the iron source.
[0017] According to an embodiment of the present application, the mixing of the sodium source, the iron source, the carbon source and the europium source comprises: ball milling the sodium source, the iron source, the carbon source and the europium source to uniformly mix the raw materials;
[0018] The rotation speed of the ball mill is 250 r / min to 800 r / min, and the time of the ball mill is 2 to 12 hours.
[0019] According to an embodiment of the present application, the inert gas includes any one of nitrogen and argon.
[0020] According to an embodiment of the present application, the sintering temperature is 280°C to 420°C;
[0021] And / or, the heating rate of the sintering is 1 to 8°C / min;
[0022] And / or, the sintering time is 5 to 15 hours.
[0023] The present application also provides a sodium ion battery, which includes the carbon-coated europium-doped sodium ferric sulfate positive electrode material described above or includes the carbon-coated europium-doped sodium ferric sulfate positive electrode material prepared by the preparation method described above.
[0024] The present application also provides an electrical device, which includes the sodium ion battery described above.
[0025] Compared with the prior art, the beneficial effects of this application include:
[0026] The present application can effectively improve the discharge specific capacity and rate performance of the positive electrode material by carbon coating and doping sodium ferric sulfate with europium.
[0027] The carbon-coated europium-doped sodium iron sulfate positive electrode material prepared in the present application has the advantage of a simple preparation process, making it easier to realize industrial production, and significantly improves the gram capacity and rate performance of the positive electrode material, showing excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0029] Figure 1 This is a comparison diagram of the XRD pattern of the carbon-coated europium-doped sodium ferric sulfate positive electrode material prepared in Example 1 and the sodium ferric sulfate standard card. DETAILED DESCRIPTION
[0030] As used herein:
[0031] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0032] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0033] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0034] In these examples, parts and percentages are by mass unless otherwise indicated.
[0035] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0036] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0037] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:
[0038] A carbon-coated europium-doped sodium ferric sulfate positive electrode material comprises a core and a carbon coating layer coating the core, wherein the core comprises europium-doped sodium ferric sulfate; since the sodium ferric sulfate itself has poor electrical conductivity and low ion transmission rate, europium source and carbon source are added during synthesis, and the added europium element replaces a small portion of the iron element, which can widen the ion transmission channel and improve the ion transmission rate. The added carbon source is coated on the surface of the sodium ferric sulfate, so that the electrical conductivity is improved, thereby improving the electrochemical performance of the sodium ferric sulfate.
[0039] The chemical formula of the carbon-coated europium-doped sodium iron sulfate positive electrode material is Na 2.4 Fe 1.8-3x Eu x (SO4)3 / C, where 0<x≤0.1, Na 2.4 Fe 1.8-3x Eu x (SO4)3 refers to the chemical formula of the core, and C refers to the chemical formula of the carbon coating. If x>0.1, the discharge specific capacity will decrease.
[0040] According to some embodiments of the present application, x may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value between 0 and 0.1.
[0041] The present application also provides a method for preparing the carbon-coated europium-doped sodium iron sulfate positive electrode material as described above, comprising:
[0042] A sodium source, an iron source, a carbon source and a europium source are mixed and sintered in an inert gas atmosphere to obtain the carbon-coated europium-doped sodium iron sulfate positive electrode material.
[0043] According to an embodiment of the present application, the sodium source includes anhydrous sodium sulfate;
[0044] The iron source includes at least one of ferrous sulfate heptahydrate, ferrous sulfate monohydrate, and anhydrous ferrous sulfate;
[0045] The carbon source comprises at least one of graphene, graphite, Ketjen black, supper p, multi-walled carbon nanotubes, citric acid, glucose, sucrose, and ascorbic acid;
[0046] The europium source includes at least one of europium sulfate and europium carbonate.
[0047] According to an embodiment of the present application, the molar ratio of sodium in the sodium source to iron in the iron source and europium in the europium source is 2.4:(1.8-3x):x.
[0048] According to an embodiment of the present application, the mass of the carbon source accounts for 1% to 12% of the total mass of the sodium source and the iron source.
[0049] According to some embodiments of the present application, the mass of the carbon source accounts for 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12% or any value between 1% and 12% of the total mass of the sodium source and the iron source.
[0050] According to an embodiment of the present application, the mixing of the sodium source, the iron source, the carbon source and the europium source comprises: ball milling the sodium source, the iron source, the carbon source and the europium source to uniformly mix the raw materials;
[0051] The rotation speed of the ball mill is 250 r / min to 800 r / min, and the time of the ball mill is 2 to 12 hours.
[0052] According to some embodiments of the present application, the number of revolutions of the ball mill can be 250r / min, 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, 600r / min, 650r / min, 700r / min, 750r / min, 800r / min or any value between 250r / min and 800r / min.
[0053] According to some embodiments of the present application, the ball milling time can be 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or any value between 2 and 12 h.
[0054] According to an embodiment of the present application, the inert gas includes any one of nitrogen and argon. Further, the purity of the inert gas may be above 99.999%.
[0055] According to an embodiment of the present application, the sintering temperature is 280°C to 420°C;
[0056] According to some embodiments of the present application, the sintering temperature may be 280°C, 300°C, 330°C, 350°C, 380°C, 400°C, 420°C or any value between 280°C and 420°C.
[0057] And / or, the heating rate of the sintering is 1 to 8°C / min;
[0058] According to some embodiments of the present application, the sintering heating rate can be 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min or any value between 1 and 8°C / min.
[0059] And / or, the sintering time is 5 to 15 hours.
[0060] According to some embodiments of the present application, the sintering time may be 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h or any value between 5 and 15 h.
[0061] The present application also provides a sodium ion battery, which includes the carbon-coated europium-doped sodium ferric sulfate positive electrode material described above or includes the carbon-coated europium-doped sodium ferric sulfate positive electrode material prepared by the preparation method described above.
[0062] The present application also provides an electrical device, which includes the sodium ion battery described above.
[0063] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0064] 1. Preparation of positive electrode materials
[0065] Example 1
[0066] Example 1 provides a carbon-coated europium-doped sodium iron sulfate positive electrode material, the preparation method of which includes:
[0067] (1) Anhydrous Na2SO4, FeSO4, and Eu2(SO4)3 were weighed according to the molar ratio of Na to Fe to Eu of 2.4:1.74:0.02, and graphene was weighed. The mass of the weighed graphene accounted for 5% of the total mass of the anhydrous Na2SO4 and FeSO4. The weighed raw materials were poured into a ball mill, and the speed was set to 300 r / min after being placed in a ball mill. The ball milling time was set for 8 hours and then started.
[0068] (2) The mixed material obtained in step (1) is taken out and placed in a tubular furnace. Argon gas is introduced, and the sintering temperature is set to 380° C., the heating rate is 2.5° C. / min, and the sintering is performed for 8 hours.
[0069] (3) The sintered product obtained in step (2) is cooled and taken out, and ball milled for 15 minutes (the rotation speed is 300 r / min) to obtain a carbon-coated europium-doped sodium iron sulfate positive electrode material, the positive electrode material comprising an inner core and a carbon coating layer coating the inner core, the inner core comprising europium-doped sodium iron sulfate, and the chemical formula of the carbon-coated europium-doped sodium iron sulfate positive electrode material is Na 2.4 Fe 1.74 Eu 0.02 (SO4)3 / C.
[0070] The XRD pattern of the positive electrode material prepared in Example 1 is as follows: Figure 1 As shown, Figure 1 The figure above is the XRD pattern of the positive electrode material prepared in Example 1. Figure 1 The picture below is a sodium ferric sulfate standard card. Figure 1 It can be seen that the crystal structure phase of carbon-coated europium-doped sodium ferric sulfate has not changed significantly compared with the sodium ferric sulfate standard card.
[0071] Example 2
[0072] Example 2 provides a carbon-coated europium-doped sodium iron sulfate positive electrode material, the preparation method of which includes:
[0073] (1) According to the molar ratio of Na element to Fe element and Eu element of 2.4:1.74:0.02, anhydrous Na2SO4, FeSO4, and Eu2(SO4)3 were weighed, and graphene and Ketjen black were weighed (the mass ratio of graphene to Ketjen black was 1:1.5). The mass of the weighed graphene and Ketjen black accounted for 5% of the total mass of anhydrous Na2SO4 and FeSO4. The weighed raw materials were poured into a ball mill, and the speed was set to 300 r / min after being placed in a ball mill. The ball milling time was set for 8 hours and then started.
[0074] (2) The mixed material obtained in step (1) is taken out and placed in a tubular furnace. Argon gas is introduced, and the sintering temperature is set to 380° C., the heating rate is 2.5° C. / min, and the sintering is performed for 8 hours.
[0075] (3) The sintered product obtained in step (2) is cooled and taken out, and ball milled for 15 minutes (the rotation speed is 300 r / min) to obtain a carbon-coated europium-doped sodium iron sulfate positive electrode material, the positive electrode material comprising an inner core and a carbon coating layer coating the inner core, the inner core comprising europium-doped sodium iron sulfate, and the chemical formula of the carbon-coated europium-doped sodium iron sulfate positive electrode material is Na 2.4 Fe 1.74 Eu 0.02 (SO4)3 / C.
[0076] Example 3
[0077] Example 3 provides a carbon-coated europium-doped sodium iron sulfate positive electrode material, the preparation method of which includes:
[0078] (1) According to the molar ratio of Na element to Fe element and Eu element of 2.4:1.77:0.01, weigh anhydrous Na2SO4, FeSO4, Eu2(SO4)3, weigh Ketjen black, and the weight of Ketjen black accounts for 5% of the total weight of anhydrous Na2SO4 and FeSO4. Pour the weighed raw materials into a ball mill, put them into a ball mill, set the speed to 300 r / min, and start ball milling for 8 hours.
[0079] (2) The mixed material obtained in step (1) is taken out and placed in a tubular furnace. Argon gas is introduced, and the sintering temperature is set to 380° C., the heating rate is 2.5° C. / min, and the sintering is performed for 8 hours.
[0080] (3) The sintered product obtained in step (2) is cooled and taken out, and ball milled for 15 minutes (the rotation speed is 300 r / min) to obtain a carbon-coated europium-doped sodium iron sulfate positive electrode material, the positive electrode material comprising an inner core and a carbon coating layer coating the inner core, the inner core comprising europium-doped sodium iron sulfate, and the chemical formula of the carbon-coated europium-doped sodium iron sulfate positive electrode material is Na 2.4 Fe 1.77 Eu 0.01 (SO4)3 / C.
[0081] Example 4
[0082] A carbon-coated europium-doped sodium iron sulfate positive electrode material was prepared by the method of Reference Example 1. The other steps were the same as those of Example 1, except that in step (1) of Example 4, anhydrous Na2SO4, FeSO4, and Eu2(SO4)3 were weighed according to a molar ratio of Na element to Fe element and Eu element of 2.4:1.5:0.1.
[0083] Example 4 A carbon-coated europium-doped sodium iron sulfate positive electrode material is prepared, the positive electrode material comprising an inner core and a carbon coating layer coating the inner core, the inner core comprising europium-doped sodium iron sulfate, and the chemical formula of the carbon-coated europium-doped sodium iron sulfate positive electrode material is Na 2.4 Fe 1.5 Eu 0.1 (SO4)3 / C.
[0084] Example 5
[0085] A carbon-coated europium-doped sodium iron sulfate positive electrode material was prepared by the method of Example 1. The other steps were the same as those of Example 1, except that in step (1) of Example 5, the mass of graphene accounted for 1% of the total mass of anhydrous Na2SO4 and FeSO4.
[0086] Example 6
[0087] A carbon-coated europium-doped sodium iron sulfate positive electrode material was prepared by the method of Reference Example 1. The other steps were the same as those of Example 1, except that in step (1) of Example 6, the mass of graphene accounted for 12% of the total mass of anhydrous Na2SO4 and FeSO4.
[0088] Comparative Example 1
[0089] In the process of preparing the positive electrode material in Comparative Example 1, no carbon source is added.
[0090] Comparative Example 1 The preparation method of the positive electrode material includes:
[0091] (1) Weigh anhydrous Na2SO4, FeSO4, and Eu2(SO4)3 according to the molar ratio of Na to Fe to Eu of 2.4:1.74:0.02, pour the weighed raw materials into a ball mill, put them into a ball mill, set the speed to 300 r / min, and start ball milling for 8 hours.
[0092] (2) The mixed material obtained in step (1) is taken out and placed in a tubular furnace. Argon gas is introduced, and the sintering temperature is set to 380° C., the heating rate is 2.5° C. / min, and the sintering is performed for 8 hours.
[0093] (3) The sintered product obtained in step (2) was cooled and taken out, and ball milled for 15 min (the rotation speed was 300 r / min) to obtain a europium-doped sodium iron sulfate positive electrode material, whose chemical formula is Na 2.4 Fe 1.74 Eu 0.02 (SO4)3.
[0094] Comparative Example 2
[0095] In the process of preparing the positive electrode material in Comparative Example 2, no europium source is added.
[0096] Comparative Example 2 The method for preparing the positive electrode material comprises:
[0097] (1) Anhydrous Na2SO4 and FeSO4 were weighed according to the molar ratio of Na element to Fe element of 2.4:1.8, and graphene was weighed. The mass of the weighed graphene accounted for 5% of the total mass of the anhydrous Na2SO4 and FeSO4. The weighed raw materials were poured into a ball mill, and the speed was set to 300 r / min after being placed in a ball mill. The ball milling time was set for 8 hours and then started.
[0098] (2) The mixed material obtained in step (1) is taken out and placed in a tubular furnace. Argon gas is introduced, and the sintering temperature is set to 380° C., the heating rate is 2.5° C. / min, and the sintering is performed for 8 hours.
[0099] (3) The sintered product obtained in step (2) is cooled and taken out, and ball milled for 15 minutes (at a rotation speed of 300 r / min) to obtain a carbon-coated sodium iron sulfate positive electrode material, wherein the positive electrode material comprises an inner core and a carbon coating layer coating the inner core, wherein the inner core comprises sodium iron sulfate, and the chemical formula of the carbon-coated sodium iron sulfate is Na 2.4 Fe 1.8 (SO4)3 / C.
[0100] Comparative Example 3
[0101] A carbon-coated europium-doped sodium iron sulfate positive electrode material was prepared by the method of Reference Example 1. The other steps were the same as those of Example 1, except that in step (1) of Comparative Example 3, anhydrous Na2SO4, FeSO4, and Eu2(SO4)3 were weighed according to a molar ratio of Na element to Fe element and Eu element of 2.4:1.35:0.15.
[0102] Comparative Example 3: A carbon-coated europium-doped sodium iron sulfate positive electrode material is prepared. The positive electrode material comprises an inner core and a carbon coating layer coating the inner core. The inner core comprises europium-doped sodium iron sulfate. The chemical formula of the carbon-coated europium-doped sodium iron sulfate positive electrode material is Na 2.4 Fe 1.35 Eu 0.15 (SO4)3 / C.
[0103] 2. Performance test of positive electrode materials
[0104] Preparation of positive electrode sheets: The positive electrode materials prepared in the embodiment and the comparative example were respectively mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 8:1:1, N-methylpyrrolidone was added and stirred evenly to form a slurry, which was evenly coated on an aluminum foil, and after drying, was punched into discs with a diameter of 16 mm, which were pressed into positive electrode sheets. The content of the positive electrode material in the positive electrode sheet was 5 to 8 mg.
[0105] Assembling button cells: The prepared positive electrode sheets were assembled into button-type sodium-ion secondary batteries of size 2025 in an Ar glove box. The assembly order was negative electrode shell, spring sheet, gasket, sodium sheet, diaphragm, positive electrode, and positive electrode shell.
[0106] The assembled battery was subjected to charge and discharge tests in the test range of 2 to 4.5 V and a rate of 0.1C to 20C. Each rate was cycled twice. The test results are shown in Table 1.
[0107] Table 1 Comparison of electrochemical performance of positive electrode materials of examples and comparative examples
[0108]
[0109] As can be seen from Table 1, the discharge specific capacity and rate performance of the positive electrode materials of Examples 1-6 are better than those of Comparative Examples 1-3. This is because the sodium ferric sulfate in Examples 1-6 is carbon-coated and doped with europium, which can effectively improve the electrochemical performance of the positive electrode material. The discharge specific capacity of the positive electrode materials of Examples 1-6 can reach more than 98 mAh / g at 0.1C, and the discharge specific capacity at 20C can also reach more than 77 mAh / g. Under the high-rate discharge conditions of 20C, the discharge specific capacity of Examples 1-6 is maintained at more than 76% relative to the discharge specific capacity at 0.1C. The sodium ferric sulfate material in Comparative Example 1 is not carbon-coated, the sodium ferric sulfate material in Comparative Example 2 is not doped with europium, and the content of europium doped in the sodium ferric sulfate material in Comparative Example 3 is too much, and the discharge specific capacity and rate performance of Comparative Examples 1, Comparative Example 2, and Comparative Example 3 are all poor.
[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0111] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A carbon-coated europium-doped sodium iron sulfate positive electrode material, characterized in that: The invention comprises a core and a carbon coating layer coating the core, wherein the core comprises sodium ferric sulfate doped with europium; The chemical formula of the carbon-coated europium-doped sodium iron sulfate positive electrode material is Na 2.4 Fe 1.8-3x Eu x (SO4)3 / C, where 0<x≤0.
1.
2. A method for preparing the carbon-coated europium-doped sodium iron sulfate positive electrode material as claimed in claim 1, characterized in that: include: A sodium source, an iron source, a carbon source and a europium source are mixed and sintered in an inert gas atmosphere to obtain the carbon-coated europium-doped sodium iron sulfate positive electrode material.
3. The method for preparing the carbon-coated europium-doped sodium iron sulfate positive electrode material according to claim 2, characterized in that: The sodium source includes anhydrous sodium sulfate; The iron source includes at least one of ferrous sulfate heptahydrate, ferrous sulfate monohydrate, and anhydrous ferrous sulfate; The carbon source comprises at least one of graphene, graphite, Ketjen black, supper p, multi-walled carbon nanotubes, citric acid, glucose, sucrose, and ascorbic acid; The europium source includes at least one of europium sulfate and europium carbonate.
4. The method for preparing the carbon-coated europium-doped sodium iron sulfate positive electrode material according to claim 2, characterized in that: The molar ratio of sodium in the sodium source to iron in the iron source and europium in the europium source is 2.4:(1.8-3x):x.
5. The method for preparing the carbon-coated europium-doped sodium iron sulfate positive electrode material according to claim 4, characterized in that: The mass of the carbon source accounts for 1% to 12% of the total mass of the sodium source and the iron source.
6. The method for preparing the carbon-coated europium-doped sodium iron sulfate positive electrode material according to claim 2, characterized in that: The mixing of the sodium source, the iron source, the carbon source and the europium source comprises: ball milling the sodium source, the iron source, the carbon source and the europium source to uniformly mix the raw materials; The rotation speed of the ball mill is 250 r / min to 800 r / min, and the time of the ball mill is 2 to 12 hours.
7. The method for preparing the carbon-coated europium-doped sodium iron sulfate positive electrode material according to claim 2, characterized in that: The inert gas includes any one of nitrogen and argon.
8. The method for preparing the carbon-coated europium-doped sodium iron sulfate positive electrode material according to any one of claims 2 to 7, characterized in that: The sintering temperature is 280°C to 420°C; And / or, the heating rate of the sintering is 1 to 8°C / min; And / or, the sintering time is 5 to 15 hours.
9. A sodium ion battery, characterized in that: The sodium ion battery comprises the carbon-coated europium-doped sodium iron sulfate positive electrode material according to claim 1 or comprises the carbon-coated europium-doped sodium iron sulfate positive electrode material prepared by the preparation method according to any one of claims 2-8.
10. An electrical device, characterized in that: The electrical equipment comprises the sodium ion battery according to claim 9.
Citation Information
Cited By
Doped sodium ferric sulfate positive electrode material as well as preparation method and application thereof
CN121687947A
Rare earth metal gradient doped polyanionic positive electrode material and preparation method and application thereof
CN122314888A
Rare earth metal gradient-doped polyanionic cathode material, and preparation method and application thereof
CN122314888B